Analisis konten integrasi TPACK berbasis STEAM pada buku tematik kelas V tema 1 organ gerak hewan dan manusia - Alifia Khaerunnisa Fajri; Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri (Didaktika Dwija Indria, 2022)
This research was conducted with the aim of analyzing the integrated content of TPACK with STEAM in thematic books. This research was conducted using a qualitative approach. The data is the form of content in thematic books. The validity of the instrument used in this study is to use expert validity calculations or Gregory and data validated by increased persistence and theoretical triangulation. Integration TPACK and STEAM in the Science aspect appears 28 items with the provision that 9 items on integration of Science with Content Knowledge and 19 on integration between Science and Pedagogical Knowledge and are the most frequent occurrences. Integration between Engineering and TPACK appears 5 items. Furthermore, content that integrates Art with TPACK is 18 items with the provision that integration between Art and Technological Knowledge is 14 items and Content Knowledge is 4 items. The integration between Technology and TPACK doesn’t appear in content class V thematic books both from teacher or student books, considering there no indicators state that the content in the book contains Technology. The Mathematics aspect did not appear with the consideration that there was no content of Mathematics subject on the theme 1 Organ Gerak hewan dan manusia.